A review of immune checkpoint inhibitor-associated myocarditis: Epidemiology, pathogenesis, and biomarkers - Le Xu; Yukai Chen; Lin Xiong; Yang Shen; Zhuolin Zhou; Siyu Wang; Ximing Xu (Human Vaccines & Immunotherapeutics)
Immune checkpoint inhibitor (ICI) have demonstrated efficacy in treating various cancers by modulating the immune system, but this can lead to immune-related adverse events (irAEs), including myocarditis. ICI-associated myocarditis is a rare but highly lethal irAE with a short mean time to onset, and difficult to diagnose early due to nonspecific symptoms and lack of biomarkers. This review highlights the need for improved recognition and management of ICI-associated myocarditis, summarizing recent advances in immunology, pathology, and biomarker research. We discuss the epidemiology, clinical features, immunological mechanisms, and roles of biomarkers in diagnosis and risk stratification. Traditional biomarkers like cTnI and hs-cTnT are sensitive but lack specificity, while emerging biomarkers like miR-155 show tissue specificity. Inflammatory markers such as NLR and CRP aid prognosis but have limited diagnostic value.